(untitled) (Jurnal Manajemen Bisnis, 2024)
This research aims to determine and analyze the influence of Persuasive Communication, Live Selling, and Product Quality on Purchase Intentions among Shopee Live Somehinc live shopping users. This research uses a quantitative approach by collecting data through distributed online questionnaires. The population in this study were Shopee Live Somethinc viewers at the 12.12 event with a sample size of 156 respondents, using a purposive sampling technique with the criteria of being Shopee users and having seen Shopee Live Something. The analysis technique uses multiple linear regression using SPSS 29. The findings of this research show that Persuasive Communication, Live Selling, and Product Quality simultaneously have a significant effect on Purchase Intention, Live Selling partially has a positive and significant influence on Purchase Intention, Product Quality partially has an influence positive and significant on Purchase Intention, while Persuasive Communication partially has a negative and insignificant effect on Purchase Intention.